2022
DOI: 10.3390/ijerph192215405
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Psychological Distress across Three Time Periods during the COVID-19 Pandemic in Poland

Abstract: Background: Since the onset of COVID-19, public health policies and public opinions changed from stringent preventive measures against spread of COVID-19 to policies accommodating life with continued, diminished risk for contracting COVID-19. Poland is a country that demonstrated severe psychological impact and negative mental health. The study aims to examine psychological impact and changes in levels of depression, anxiety, and stress among three cross-sectional samples of Polish people and COVID-19-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Future research where longitudinal prospective studies are needed to rule out alternative explanations of the observed effects. For example, Chudzicka-Czupala et al (2022) showed that a reduction in the level of the measured subjective distress and in the frequency of checking COVID-19 news-related information across three periods during the pandemic in Poland. These results indicated that individuals' cognition and behavior will change with the surrounding environment.…”
Section: Limitations and Future Directionmentioning
confidence: 99%
“…Future research where longitudinal prospective studies are needed to rule out alternative explanations of the observed effects. For example, Chudzicka-Czupala et al (2022) showed that a reduction in the level of the measured subjective distress and in the frequency of checking COVID-19 news-related information across three periods during the pandemic in Poland. These results indicated that individuals' cognition and behavior will change with the surrounding environment.…”
Section: Limitations and Future Directionmentioning
confidence: 99%
“…People holding undergraduate degrees, those working in sectors other than healthcare and those having specific term work contracts had a higher likelihood of income reduction. In another study, (Chudzicka‐Czupała et al, 2022), 2324 Polish persons participated in three cross‐sectional studies from March 2020 to December 2021. Findings were that physical symptoms such as, chills, myalgia and fatigue were significantly associated with higher depression, anxiety and stress.…”
Section: Media Exposure To Violence and Psychological Reactionsmentioning
confidence: 99%
“…Recent findings indicated a reduction in the level of the measured subjective distress and frequency of checking COVID-19-related news and information across three periods during the pandemic in Poland (Chudzicka-Czupała et al, 2022). However, at the same time, female sex, student status, and physical symptoms, such as chills, myalgia, and fatigue, demonstrated significant association with high stress (Chudzicka-Czupała et al, 2022). Other studies have found that satisfaction with work and family life has dropped significantly during the lockdown (Bartoszek et al, 2020;Gawrych et al, 2021;Möhring et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, longitudinal evidence shows that there were no significant changes in the prevalence of moderate-to-severe stress (8.1%), anxiety (28.8%), and depression (16.5%) in China (Wang et al, 2020b). Recent findings indicated a reduction in the level of the measured subjective distress and frequency of checking COVID-19-related news and information across three periods during the pandemic in Poland (Chudzicka-Czupała et al, 2022). However, at the same time, female sex, student status, and physical symptoms, such as chills, myalgia, and fatigue, demonstrated significant association with high stress (Chudzicka-Czupała et al, 2022).…”
Section: Introductionmentioning
confidence: 99%